(untitled) (Olhar de Professor, 2022)
The Education of the Countryside has the mission of consolidating a Formal Education and specific to the people of the countryside. Thus, we aim to focus on the discussion of two fundamental principles in the training of rural teachers: a) Field and Society Project b) Alternation. For that, we used content analysis of the Political-Pedagogical Projects of five Brazilian Federal Universities. All the documents analyzed presented the need for plural teacher training to build an education focused on understanding the social context of the subjects, thereby seeking to transform their realities. All courses are organized in Alternation Regime, which is the articulation between Tempo-Comunidade (TC) and Tempo-Universidade (TU) or Tempo-Escola (TE) and has its curricular organization established in nuclei / domains.v